Antibacterial and antiviral evaluation of sulfonoquinovosyldiacylglyceride: a glycolipid isolated from Azadirachta indica leaves. (6th November 2013) - Bharitkar, Y.P.; Bathini, S.; Ojha, D.; Ghosh, S.; Mukherjee, H.; Kuotsu, K.; Chattopadhyay, D.; Mondal, N.B.
Abstract Assessment of antibacterial as well as antiherpes virus activity of sulfonoquinovosyldiacylglyceride (SQDG), a glycolipid, isolated from the leaves of Azadirachta indica has been described. Antimicrobial activity was evaluated against Gram‐positive, Gram‐negative bacteria and herpes simplex virus. SQDG showed significant inhibitory activity against Salmonella typhi and two isolates of Shigella dysenteriae with MIC values 32 μg ml−1, while three isolates of Salm. typhi, Escherichia coli and Vibrio cholerae were inhibited at 64 μg ml−1 and have shown zone diameter ranging from 6·2 to 12·3 mm. The growth kinetics study of SQDG on Salm. typhi and Sh. dysenteriae revealed that the growths were completely inhibited at their MIC values within 24 h of exposure. Interestingly, SQDG inhibits herpes simplex virus (HSV) type 1 and 2 with the EC50 of 9·1 and 8·5 μg ml−1, compared with acyclovir (2·2 and 2·8 μg ml−1 against HSV‐1 and HSV‐2). The selectivity index (SI) was found to be 12·4 against HSV‐1 and 13·41 with HSV‐2. Furthermore, the expression of proinflammatory cytokines of HSV‐infected and SQDG‐treated macrophages using ELISA kit revealed that SQDG significantly downregulated the production of TNF‐α, IL‐1β, IL‐12 and IL‐6. Significance and Impact of the Study The water‐soluble metabolite sulfonoquinovosyldiacylglyceride (SQDG) isolated from Azadirachta indica (Neem) possess significant antibacterial as well as anti‐HSV activity. The efficacies as well as the solubility factor of SQDG substantiate a greater attention for its use as phytotherapeutic drug for controlling microbial infections as most consumers have better acceptance of phytomedicines than synthetic drugs.